2013
DOI: 10.7314/apjcp.2013.14.4.2167
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer Detection by Screening - Presenting Circulating miRNAs as a Promising Next Generation Biomarker Breakthrough

Abstract: Lung cancer remains a major cause of morbidity and mortality worldwide, accounting for more deaths than any other cause. All the clinical practice guidelines recommended against routine screening for lung cancer have cited lack of robust evidence, at least until a few years back. However, the potential to screen lung cancers has received renewed interest due to superior performance of low dose CT (LD-CT) in detecting early stage cancers. The incremental costs and risks involved due to the invasive procedures i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 40 publications
(34 reference statements)
3
16
0
Order By: Relevance
“…At present CEA is mainly used in the diagnosis of gastrointestinal cancer, however, it is reported that the sensitivity of CEA is around 35% to 77% (Ramshankar et al, 2013), our study suggested that the sensitivity of CEA in detecting lung cancer was 39.45%, and the specificity was 73.53%, that is in accordance with previous reports. Another finding of our study is that serum CEA in patients with lung cancer were significantly higher than those with benign disease and healthy controls (p< 0.05), indicating that CEA could be used in early diagnosis of lung cancer.…”
Section: Discussionsupporting
confidence: 82%
“…At present CEA is mainly used in the diagnosis of gastrointestinal cancer, however, it is reported that the sensitivity of CEA is around 35% to 77% (Ramshankar et al, 2013), our study suggested that the sensitivity of CEA in detecting lung cancer was 39.45%, and the specificity was 73.53%, that is in accordance with previous reports. Another finding of our study is that serum CEA in patients with lung cancer were significantly higher than those with benign disease and healthy controls (p< 0.05), indicating that CEA could be used in early diagnosis of lung cancer.…”
Section: Discussionsupporting
confidence: 82%
“…With the development of genomic and basic research, increasing numbers of cell molecular biomarkers have been considered as specific diagnosing and targeted therapeutic agents for lung cancer (Uribe and Gonzalez, 2011;Hirose et al, 2012;Brothers et al, 2013;Ramshankar and Krishnamurthy, 2013;Wang et al, 2013). However, clear molecular biomarkers for the clinical diagnosis and treatment of lung cancer have not been identified.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of miR-101 and Cox-2 were negatively correlated in cervical cancer of Uyghur women, which may serve as biomarkers of diagnosis markers for cervical cancer in Uyghur women which provide direct experimental evidence for the roles of miRNA in diagnosis of cancer. Meanwhile, blood based tests for screening purposes or disease monitoring would be more suitable as they are minimally invasive, relatively have low cost and can be repeated as well (Ramshankar and Krishnamurthy, 2013). Because of this, Ramshankar and Krishnamurthy (2013) reported that the circulating miRNAs present in both serum and plasma as attractive candidates to be used as cancer biomarkers and could serve as non-invasive biomarkers for early detection and diagnosis of lung cancer.…”
Section: Micrornas As Potential Biomarkers For Cancer Diagnosis and Pmentioning
confidence: 99%